Effectiveness of Garlic Extract Pesticide (Allium sativum) Against Leaf Films in Saws (Brassica juncean) - Raja Siti Aisyah; Syaprina Anggraini; Zahwa Adiesty; Indayana Febriani Tanjung; Febry Ramadhani (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
Indonesia has a large part of its territory in the form of agricultural land which results in some of its people working as farmers. Land processing and maintenance in the agricultural sector were found to be obstacles so that production decreased from what it should have been. This is the reason why the number of requests for crops cannot be fulfilled, which results in an increase in prices. The method used in a non-factorial Completely Randomized Design (CRD) by carrying out 4 comparisons of pesticide concentrations including K1 (10 cc of onion extract mixed with 90 ml of water), K2 (15 cc of onion extract mixed with 85 ml of water), K3 (20 cc of onion extract mixed with 80 ml of water), K4 (25 cc of onion extract mixed with 75 ml of water), K5 (30 cc of onion extract mixed with 70 ml of water). The materials used in this study included garlic extract and water. The tools used are hoes, soil testers, thermometers, gembor, measuring tools and dippers. The conclusion from this study was that the concentration comparison was carried out that the V treatment (30 cc + 70 ml liters of water) was effective in the use of natural garlic pesticides (Allium sativum) by reducing the number of leaf pests on mustard greens (Brassica juncean) by 23 individuals for 2 week of observation and 2 times of spraying.